Toxic Epidermal Necrolysis: Case Report and Review - Breshkovska, Hristina; Duma, Silvija; Nikolovska, Suzana; Dohcheva Karajovanov, Ivana; Mitrova Telenta, Julija; Duma, Hristian; Gjorgjeska, Andrijana; Trajkova, Vesna; Peneva, Margarita (Scientific Foundation SPIROSKI, Skopje, Republic of Macedonia, 2024)
Stevens–Johnson syndrome and toxic epidermal necrolysis (TEN) are severe mucocutaneous adverse drug reactions primarily caused by drugs. Characterized by fever, prodromal symptoms, and extensive epidermal sloughing with mucous membrane involvement (>90%), they are collectively termed epidermal necrolysis and are considered a disease continuum.CASE PRESENTATION: A65-year-old man presented with widespread erythema and distinctive target-like lesions, accompanied by ruptured flaccid vesicles on the extremities. Following a 4-week carbamazepine treatment for a previous cerebrovascular insult, hematological analysis revealed abnormalities. Amultidisciplinary team, including a neurologist, endocrinologist, and ophthalmologist, prescribed a 3-day course of intravenous immunoglobulin at 0.5g/kg and an initial dose of 300mg prednisolone for 3days, supported by additional therapy. Discharged after 3weeks, the rash completely resolved within 2months. CONCLUSION: TEN, a severe mucocutaneous condition with a 30% mortality rate, often results from drug exposure. Swift identification of the causative drug is crucial for optimal outcomes. Treatment primarily includes discontinuing the offending drug and offering supportive care for mucocutaneous lesions. Amultidisciplinary approach is vital based on organ system involvement. The effectiveness of pharmacological treatments, such as intravenous immunoglobulin and corticosteroids, is continually under evaluation.
Keywords: Stevens–Johnson syndrome; Toxic epidermal necrolysis; Mucocutaneous reaction; Carbamazepin